Kinetics and Characterization of Microalgae Biofuel by Microwave-assisted Pyrolysis Using Activated Carbon - Viqhi Aswie; Lailatul Qadariyah; Mahfud Mahfud (Journal of Engineering and Technological Sciences, 2022)
The reaction kinetics and the effect of power on microwave-assisted pyrolysis (MAP) in converting microalgae to biofuel were investigated to determine the decomposition mechanism and then characterize the best product. The resulting product consisted of three phases, namely liquid phase (bio-oil), solid residue (char), and uncondensable gas products. The results showed that the optimal increase in microwave power obtained was 20.57% with a 600-watt microwave power condition, a reaction time of 20 minutes, a microwave absorber to microalgae ratio of 1:6, and a heating rate of 25.96 K/min (600 watts). The reaction kinetics evaluated in the best condition showed a second-order reaction with activition energy (Ea) and pre-exponential factor (A) at 35.5971 kJ/moles and 2,606.75/minute, respectively. The characteristics of the biofuel product obtained were 1.01 gr/mL density, viscosity 10.97 cP, and pH 9.30. In addition, based on GC-MS analysis, the bio-oil contained aliphatic, aromatic, phenol, FAME, and polycyclic aromatic hydrocarbon (PAH) organic compounds. These results indicate that MAP has the potential to be developed as an alternative production process for biofuels.